Role of Dexmedetomidine on post-traumatic stress response - Jawad Hameed; Amjid Ali; Ayesha Mairaj; Hadiqa tul Batool; Abid Haleem Khattak; Mushafa Majeed (Medical Journal of South Punjab, 2024)
Objective: to explore the role of dexmedetomidine on the incidence of postoperative post traumatic stress response (PTSD) in trauma patients in the emergency department. Methods: This randomized clinical trial was carried out at Lady Reading Hospital Peshawar from January 2023 to October 2023. Participants were randomly assigned to receive either normal saline or dexmedetomidine. The study medications included 2ml normal saline or dexmedetomidine 200 ?g/2 mL. Results: Postoperative NRS score of normal saline and dexmedetomidine group at day 1 was 4.57±1.79, at day 2 2.66±1.23, and at day was 3 1.84±0.41 gradually decreased, and in dexmedetomidine group, low NRS score was found at day 1 it was 3.09±1.03, at day 2 it was 2.33±0.49 and at day 3 it was 0.59±0.11. Postoperative BAI score was gradually decreased from day 1, 2 and day 3, and BAI score was low in dexmedetomidine group as compared to the normal saline group, (p<0.050). Conclusion: The use of dexmedetomidine intraoperatively has been shown to decrease the post-operative stress in patients of trauma. Dexmedetomidine can be used in emergency traumatic surgeries for sedation and to overcome the post operative complications and stress.